TRAIL-R1-Targeted CAR-T Cells Exhibit Dual Antitumor Efficacy - Nai, Yaru; Du, Li; Shen, Meiying; Li, Tingting; Huang, Jingjing; Han, Xiaojian; Luo, Feiyang; Wang, Wang; Pang, Da; Jin, Aishun (Frontiers in Molecular Biosciences, 2021)
Tumor necrosis factor-related apoptosis-inducing ligand receptor 1 (TRAIL-R1) has limited expression in normal tissues but was highly expressed in various types of tumors, making it an attractive target for cancer immunotherapy. Here, we utilized the single chain variable fragment (scFv) from our previously identified TRAIL-R1 targeting monoclonal antibody (TR1419) with anti-tumor efficacy, and produced the TR1419 Chimeric antigen receptor (CAR) T cells. We characterized the phenotypes and functions of these CAR-T cells and found that the third-generation TR1419-28BBζ CAR-T cells exhibited greater target sensitivity and proliferative capability, with slightly higher PD-1 expression after antigen stimulation. Importantly, we found that the TR1419 CAR-T cells could induce TRAIL-R1 positive tumor cells death via a dual mechanism of the death receptor-dependent apoptosis as well as the T-cell mediated cytotoxicity. Altogether, the TR1419 CAR-T cells could serve as a promising strategy for targeting the TRAIL-R1 positive tumors.